Diseño de patrones y estrucuras compositivas, a partir de una colección de cerámica Panzaleo para ser aplicados en un emprendimiento. - Atavallo Pullopaxi, Alexander Danilo (2019)
The research area of the graphic design major develops the "Panzaleo project," whose purpose is to contribute to the renovation of local graphics, strengthening cultural expressions and disseminating the heritage relics of the sector through graphic design. Professors and students are immersed in this project, so its starting point has the following question: how to create designs of patterns and compositional structures from the collections of pre-Columbian ceramics belonging to the museums of the "Hacienda San Juan Bautista de Tilipulo" and the "Isidro Ayora School" in Latacunga city to be used as graphic references in ventures? To contribute to the solution to this problem, the following objective is proposed: Design patterns and compositional structures from the Panzaleo ceramic collections through Foundations and graphic design techniques. To achieve this objective, the texts of Graphic Design Thinking and the New Fundamentals of Graphic Design by author Ellen Lupton were used which guided this work in the creation of forms, through their design techniques. Visual speculation helped organize ceramic pieces according to their shape. The brainstorming was the starting point for the design of patterns and compositional structures. This research has the purpose of contributing to the diffusion of the Cotopaxi cultural identity, through the iconographic use of the pieces of the Panzaleo Culture collections and, the same way, these serve as a source of inspiration for the creation of new creative enterprises through graphic design. As a final result, a digital and printed interactive catalog was obtained. It shows the different designs, mockup, and possible applications, as well as the project, concludes with a guide to the creation of these patterns and the catalog. In this way, it is hoped that the Panzaleo iconography will be disseminated throughout the community of the Cotopaxi Technical University, and the creative entrepreneurs of the Latacunga city, who are artisans and designers.